Determinants associated with anemia level among children under 5 years in Gambia: a structural equation modelling approach - Akindutire, Opeyemi Roselyn; Ramroop, Shaun; Habyarimana, Faustin (Frontiers in Public Health, 2025)
IntroductionAnemia remains a public health concern globally in industrialized and developing nations, especially for children under five. It is still the leading cause of illness and mortality, which is harmful, especially in children from developing countries. Furthermore, children’s emotional, physical, and mental health can be negatively impacted by anemia if it is not addressed promptly. Researchers have unraveled the intricate relationships between components using Structural Equation Modelling (SEM).ObjectiveTherefore, using anemia as the main variable, this study intends to use SEM to investigate the association between socioeconomic and household resources and the anemic health status of under-five children in Gambia. The Demographic Health Survey website provided the data for this investigation.MethodsTwenty-one factors were included in the observations 8,362 utilized in this study and categorized into socioeconomic factors, child’s environmental factors, and household resources. These variables are sex, type of place of residence, marital status, anemia level, type of toilet facility, location of water source, income status, place of residence, month of birth, state, sources of drinking water, and the respondents’ highest level of education. The model specification for the SEM model used shows anemia status level as the dependent variable against income status, parent’s highest educational level, parent’s sex, location of source of water, number of eligible children, state, source of drinking water, parent’s marital status, child’s age and location of toilet facility of the respondents.ResultsThe results indicate that parental educational attainment significantly influences children’s hemoglobin levels. The findings indicate that the following factors significantly affect children’s anemia levels: housing location, type of restroom, gender, highest level of education, water source location, marital status, drinking water source, state, number of eligible children, and income status at p-value (p < 0.000) deliberately.Unique contributionThe present study has a unique impact of socio-economic factors and human resources on anemia. It would be helpful to consider factors with policy implications for the betterment of anemia patients’ wellbeing.